Meta‐analysis of ischaemic preconditioning for liver resections. Issue 13 (December 2013) - O'Neill, S.; Leuschner, S.; McNally, S. J.; Garden, O. J.; Wigmore, S. J.; Harrison, E. M.
<x xml:space="preserve">Abstract</x> Background Vascular clamping reduces blood loss during liver resection but leads to ischaemia–reperfusion injury. Ischaemic preconditioning (IP) may reduce this. This study aimed to evaluate IP in liver resection under clamping. Methods This was a systematic review and meta‐analysis of randomized clinical trials (RCTs) evaluating IP in adults undergoing liver resection under either continuous clamping (CC) or intermittent clamping (IC). Primary outcomes were mortality, liver failure and morbidity. Secondary outcomes included duration of operation, blood loss, length of hospital stay, length of intensive therapy unit stay, transfusion requirements, prothrombin time, and bilirubin and aminotransferase levels. Weighted mean differences were calculated for continuous data, and pooled odds ratios (ORs) for dichotomous data. Results were produced with a random‐effects model with 95 per cent confidence intervals (c.i.). Results A total of 2960 records were identified and 11 RCTs included 669 patients (IP 331, control 338). No significant difference in mortality (6 RCTs; IP 186, control 190; OR 1·36, 95 per cent c.i. 0·13 to 13·68; P = 0·80) or morbidity (6 RCTs; IP 186, control 190; OR 0·58, 0·31 to 1·07; P = 0·08) was found for IP plus CC versus CC. Nor was there a significant difference in mortality (4 RCTs; IP 122, control 121; OR 1·33, 0·24 to 7·32; P = 0·74) or morbidity (4 RCTs; IP 122, control 121; OR 0·87, 0·52 to 1·47; P = 0·61) for IP plus (CC or IC) versus IC. No significant differences were found for secondary outcome measures. Conclusion This meta‐analysis failed to find a significant benefit of IP in liver resection.